2011
DOI: 10.2215/cjn.04560510
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin, a Surrogate Marker of Vasopressin, Is Associated with Disease Severity in Autosomal Dominant Polycystic Kidney Disease

Abstract: SummaryBackground and objectives Experimental studies suggest a detrimental role for vasopressin in the pathogenesis of autosomal dominant polycystic kidney disease (ADPKD). However, it is unknown whether endogenous vasopressin concentration is associated with disease severity in patients with ADPKD.Design, setting, participants, & measurements Plasma copeptin concentration (a marker of endogenous vasopressin levels) was measured in 102 ADPKD patients (diagnosis based on Ravine criteria) by an immunoassay. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 49 publications
4
64
1
2
Order By: Relevance
“…These data support earlier reports in ADPKD, 43 and the general population, although the significance levels were lower in our study. 49,50 This can be due to the higher number of patients in those studies, the fact that the PREVEND study used a cutoff of 10 mg/L albuminuria for inclusion, and the Malmo study analyzed ACR in spot urine instead of 24-hour urine collection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These data support earlier reports in ADPKD, 43 and the general population, although the significance levels were lower in our study. 49,50 This can be due to the higher number of patients in those studies, the fact that the PREVEND study used a cutoff of 10 mg/L albuminuria for inclusion, and the Malmo study analyzed ACR in spot urine instead of 24-hour urine collection.…”
Section: Discussionsupporting
confidence: 92%
“…This association has been observed in prospective studies involving patients with ADPKD as well as patients with a renal transplant and patients with diabetes. [43][44][45][46][47][48] Only two studies have used a populationbased sample to test the hypothesis that AVP might be involved in the development of albuminuria. In the Prevention of Renal and Vascular Endstage Disease (PREVEND) study, which includes 7593 nondiabetic participants with an urinary albumin concentration $10 mg/L, circulating copeptin was positively associated with albuminuria and negatively with renal function in a cross-sectional analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ddvap, desmopressin. study in 102 ADPKD patients, we found that copeptin levels were associated with various markers of disease severity, among which albuminuria, GFR, renal blood flow, and total renal volume (33). In a prospective study in 79 ADPKD patients, we subsequently showed that baseline copeptin levels were associated with faster kidney function decline when assessed as the change in either iothalamate clearance during short-term follow-up or eGFR during long-term follow-up (W.E.…”
Section: Discussionmentioning
confidence: 99%
“…In ADPKD, several urinary (and plasma) markers have been recently reported, e.g., NGAL, CCL2 (MCP-1), CD14, AVP (copeptin) and HAVCR1 (KIM-1; Bolignano et al 2007;Kuehn et al 2007;Meijer et al 2010Meijer et al , 2011Zheng et al 2003). However, these markers have not made it into the clinic as yet and have also been reported to overlap with acute kidney injury patients and healthy controls thus raising concerns regarding their specificity (Kistler et al 2013).…”
Section: Adpkd Biomarkersmentioning
confidence: 99%